Penggunaan Media Sosial Sebagai Wadah Promosi UMKM di Desa Bojongkulur - Muriyah Muriyah; Amelia Nur karomah; Anindya Rifqah Purwanti; Siti Halimatusya’diah; Novi Indriyani; Ghista Viona Banowati; Febrianti Febrianti (FKIP, Universitas Palangka Raya, 2025)
This community service program aims to enhance digital literacy and online marketing skills for Micro, Small, and Medium Enterprises (MSMEs) in Bojongkulur Village. The activity focuses on utilizing digital platforms such as GoFood and GrabFood as tools to expand the marketing reach of MSME products. The methods employed include counseling, training, and direct mentoring. The program results indicated an increased understanding of digital platforms among MSMEs and a rise in the number of MSMEs registered as partners. Challenges encountered include the initial lack of digital literacy among some MSMEs and limitations in supporting devices.